Electrospun Biomimetic Multifunctional Nanofibers Loaded with Ferulic Acid for Enhanced Antimicrobial and Wound-Healing Activities in STZ-Induced Diabetic Rats - Sneha Anand; Prashant Pandey; Mohammed Yasmin Begum; Kumarappan Chidambaram; Dilip Kumar Arya; Ravi Kr. Gupta; Ruchi Sankhwar; Shweta Jaiswal; Sunita Thakur; Paruvathanahalli Siddalingam Rajinikanth (MDPI AG, 2022)
Diabetic foot ulceration is the most distressing complication of diabetes having no standard therapy. Nanofibers are an emerging and versatile nanotechnology-based drug-delivery system with unique wound-healing properties. This study aimed to prepare and evaluate silk-sericin based hybrid nanofibrous mats for diabetic foot ulcer. The nanofibrous mats were prepared by electrospinning using silk sericin mixed with different proportions of polycaprolactone (PCL) and cellulose acetate (CA) loaded with ferulic acid (FA). The in vitro characterizations, such as surface morphology, mechanical properties, swelling behavior, biodegradability, scanning electron microscopy, and drug release were carried out. The SEM images indicated that nanofibers formed with varied diameters, ranging from 100 to 250 nm, and their tensile strength was found to range from 7 to 15 MPa. In vitro release demonstrated that the nanofibers sustained FA release over an extended time of period. In vitro cytotoxicity showed that the nanofibers possessed a lower cytotoxicity in HaCaT cells. The in vivo wound-healing studies demonstrated an excellent wound-healing efficiency of the nanofibers in diabetic rats. Furthermore, the histopathological studies showed the nanofibers' ability to restore the skin's normal structure. Therefore, it was concluded that the prepared silk-sericin-based hybrid nanofibers loaded with FA could be a promising drug-delivery platform for the effective treatment of diabetic foot ulcers.